THE INFLUENCE OF BUDGET PALNNING ON FINANCIAL MANAGEMENT AND FINANCIAL PERFORMANCE - Yusni Marsan; Salju; Rahmawati; Goso (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study investigates the relationship and impact of budget planning on financial management and financial performance, emphasizing the novel discovery of budget disparities within these processes. Utilizing a quantitative approach, the research employs Partial Least Squares (PLS) analysis on a sample from 2021-2023, encompassing 4 programs and 14 activities related to budget planning, financial management, and financial performance. Budget planning is assessed using the Priority of the Parallel Budget Ceiling (PPAS), financial management is evaluated through the Budget Disclosure Document (DPA), and financial performance is measured using the Budget Realization Report (LRA). The results indicate that the Cronbach’s Alpha values for the three variables exceed 0.70, demonstrating reliability. The R Square value for Financial Performance is 0.997, while Financial Management has an R Square value of 0.999. The direct effect of Budget Planning on Financial Performance is 0.998, and on Financial Management, it is 1.000. These findings suggest that while Budget Planning has a positive influence on both Financial Management and Financial Performance, the effect is not significant. The novelty of this study lies in its identification of budget disparities and their implications for regional financial management and performance, a topic previously underexplored in the literature.